Success under pressure: the role of competitive and market forces in equity crowdfunding campaigns: evidence from Poland - Artur A. Trzebiński; Kamil Gemra (Future Business Journal)
Abstract This study explores how competition and macroeconomic factors affect the success of equity-based crowdfunding campaigns (ECF). Using a dataset of 247 campaigns from multiple platforms in Poland, we use logistic, Tobit and fixed-effects panel regressions to evaluate the impact of within-platform and between-platform competition, as well as market indicators such as interest rates, the number of initial public offerings (IPOs) and the NewConnect index, on funding outcomes. Our results reveal that within-platform competition significantly decreases both the likelihood of campaign success and the percentage of the funding target achieved, suggesting fragmentation of investor attention. The effects of macroeconomic variables are mixed. While interest rates do not consistently impact success, both IPO frequency and the NewConnect index are positively associated with funding outcomes. This study contributes to the crowdfunding literature by incorporating competitive and macroeconomic dimensions and provides policy insights into improving investor engagement and campaign performance.